2006
DOI: 10.5194/hess-10-321-2006
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model of daily water balance following partial clearing from forest to pasture

Abstract: Abstract.A simple conceptual water balance model representing the streamflow generation processes on a daily time step following land use change is presented. The model consists of five stores: (i) Dry, Wet and Subsurface Stores for vertical and lateral water flow, (ii) a transient Stream zone Store (iii) a saturated Goundwater Store. The soil moisture balance in the top soil Dry and Wet Stores are the most important components of the model and characterize the dynamically varying saturated areas responsible f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…Variable source areas are formed when perched or permanent groundwater tables intersect the ground surface. Saturation excess runoff from variable source areas is considered to be an important mechanism of streamflow generation in the jarrah forest (Stokes, 1985;Ruprecht and Schofield, 1989; Bari and Smettem, 2006). Ruprecht and Schofield (1989) found that, following clearing of Wights catchment in the high rainfall zone of the jarrah forest for agriculture, a significant component of the increased streamflow was correlated with expansion of the groundwater-induced variable source area.…”
Section: Methodsmentioning
confidence: 99%
“…Variable source areas are formed when perched or permanent groundwater tables intersect the ground surface. Saturation excess runoff from variable source areas is considered to be an important mechanism of streamflow generation in the jarrah forest (Stokes, 1985;Ruprecht and Schofield, 1989; Bari and Smettem, 2006). Ruprecht and Schofield (1989) found that, following clearing of Wights catchment in the high rainfall zone of the jarrah forest for agriculture, a significant component of the increased streamflow was correlated with expansion of the groundwater-induced variable source area.…”
Section: Methodsmentioning
confidence: 99%
“…In hydrologic modelling, many researchers have discussed the use and application of different hydrologic models such as water balance, regression analysis, energy budget and other empirical models (Tabios 1978;Arnell 1999;Vogel et al 1999;Fleming and Neary 2004;Young 2006; Bari and Smettem 2006). The application of a typical hydrologic model requires calibration and parameter fitting for a given site.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we explore the concept of PES for improvements in water quality brought about by reforestation, in the Warren-Tone watershed (WT) of south-west Western Australia, which has a well-calibrated hydrological response model (LUCICAT) (Bari and Smettem, 2006a, b). LUCICAT has consistently provided good estimates of monthly streamflow, with Nash-Sutcliffe Criteria over 0.8 in all cases and over 0.9 for over 80% of watersheds modelled (Bari and Smettem, 2006a). The LUCICAT hydrological model provides two major outputs: water yield and water quality in response to landuse.…”
Section: Introductionmentioning
confidence: 86%